Protective Effect and Potential Mechanism of Simvastatin on Myocardial Injury Induced by Diabetes with Hypoglycemia - Li, Haiqing; Zhao, Qianqian; Liu, Rong; Yang, Lan; Chen, Huanzhen; Cui, Xiangli (Experimental and Clinical Endocrinology & Diabetes, 2018)
Background Simvastatin has been reported to reduce cardiovascular related morbidity and mortality in clinical trials which was independent of its cholesterol-lowering effect. This study aims to investigate the protective effect of simvastatin on myocardial injury caused by diabetic hypoglycemia and the possible underlying mechanism.Methods We used streptozotocin (STZ) at a dose of 55 mg/kg to induce diabetes mellitus (DM) and over-dose insulin to induce hypoglycemia to establish diabetic hypoglycemia rat models. The cardiac protective effect of simvastatin treatment (at a dose of 40 mg/kg·d) upon diabetic hypoglycemia models was assessed. Ex vivo cardiac function, cardiomyocyte inotropic property and calcium transient were evaluated. The expression levels of microRNA (miRNA) and NF-κB in heart tissues were investigated.Results Both systolic and diastolic functions in diabetic rats were weakened, and further worsened in diabetic hypoglycemia rats, partially restored after administration of simvastatin. The protective effect of simvastatin on cardiac function under diabetic hypoglycermia was associated with decreased intracellular calcium and increased calcium sensitivity. miRNA array showed a differential profile of miRNA expression existed in diabetic hypoglycemia rats compared with diabetic non-hypoglycemia group, and that simvastatin could reverse the altered miRNA expression in diabetic hypoglycemia group.Conclusion Simvastatin has protective effect on myocardial injury caused by diabetes with hypoglycemia, which is associated with increased calcium sensitivity, decreased NF-κB expression and altered miRNA expression profile.
Keywords: diabetic hypoglycemia; simvastatin; cardiac dysfunction; NF-κB; miRNA